2003
DOI: 10.1111/1468-0092.t01-1-00004
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of republican amphorae in france

Abstract: Recent research on assemblages of Republican amphorae from France has greatly altered our understanding of the wine trade during the Late Iron Age. However, much of this work, and its implications, are not well known in Britain and this paper aims to disseminate this information by examining the latest evidence concerning the dating and distribution of Republican amphorae (Dressel 1, Lamboglia 2, Brindisi and Republican Ovoid amphorae) in France during the Late Iron Age. In total 1975 findspots of Republican a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 31 publications
0
11
0
1
Order By: Relevance
“…2007b). Although earlier ‘Greco‐Italic’ amphorae have been reported throughout non‐Mediterranean France (Loughton 2003; Poux 2004), on closer inspection it now appears that few are from La Tène C2 or D1a contexts ( c .200–130 BC) 2 and the majority of findspots are later (Loughton forthcoming a; Deberge et al. 2007b) (Fig.…”
Section: Chronology: Early or Late?mentioning
confidence: 92%
See 2 more Smart Citations
“…2007b). Although earlier ‘Greco‐Italic’ amphorae have been reported throughout non‐Mediterranean France (Loughton 2003; Poux 2004), on closer inspection it now appears that few are from La Tène C2 or D1a contexts ( c .200–130 BC) 2 and the majority of findspots are later (Loughton forthcoming a; Deberge et al. 2007b) (Fig.…”
Section: Chronology: Early or Late?mentioning
confidence: 92%
“…Recent studies have suggested that the Republican wine trade to non‐Mediterranean France commenced as early as the late third or early second century BC (Barthélémy‐Sylvand 2005; Maza 1998; Lemaître et al. 2007; Loughton 2000; 2003; Loughton and Jones 2000; Poux 1999a; 2004). It is becoming possible to date the start of the Republican wine trade and its chronology with greater precision because of the increasing number of detailed regional studies of Republican amphora assemblages and associated finds (e.g.…”
Section: Chronology: Early or Late?mentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, these have been associated with the increasing involvement of Rome in southern Gaul from the start of the second century BC (Dietler, 1997), accompanied by a striking increase in the circulation of Roman goods northward into Gaul, the Rhineland, and the upper Danube region (Loughton, 2003), and later by the establishment of the Roman province of Gallia Narbonensis around 120 BC. Archaeologically, the clearest change is the construction of walled settlements known as oppida (Collis, 1995).…”
Section: Centralization Processesmentioning
confidence: 99%
“…Tipoló-gicamente, pensamos que el ejemplar procedente de las Figura 24. Tipos ovoides brindisinos relacionables con el tipo Ovoide 6 del Guadalquivir.Arriba: Apani (Palazzo 1989), Ostia (Panella 1973), Galia (Loughton 2003). Abajo: Giancola (Manacorda 2001), Agde (Cipriano y Carre 1989), Planier 3 (Tchernia 1968(Tchernia -1970, Apani (Palazzo 1989 (Panella 1973: 494-496;625, fig.…”
unclassified